Masakimia : A Mobile Application Learning Chemical Substance for Chemistry Students - Norazamai, Adam Iskandar; Ali, Nor Azlina (Journal of Computing Technologies and Creative Content, 2025)
This research paper addresses the necessity for a mobile learning application tailored to Malaysian chemistry students through the ”MasaKimia” (MK) project. The project aims to revolutionize chemistry education via an interactive mobile application. MK is designed to provide an engaging and effective learning experience by featuring an interactive periodic table, quiz games, and digital flashcards. Aligned with the latest Malaysian chemistry curriculum, this project seeks to bridge the gap in accessible, high-quality mobile learning resources for students. The anticipated outcome, the MK mobile learning application, promises to be a comprehensive and engaging edu- cational tool, poised to significantly enhance chemistry education in Malaysia. This paper envisions a future where technology and education converge, delivering a transformative learning experience and ensuring no student is left behind in their pursuit of knowledge.